HUBUNGAN PENGUASAAN STRUKTUR KALIMAT DAN KEMAMPUAN BERPIKIR KRITIS DENGAN KETERAMPILAN MENULIS EKSPOSISI SISWA KELAS V SD - Annisa Arma Harningrum; Gusti Yarmi; Juhana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to determine the correlation, either partially or simultaneously, of the students’ sentence structure mastery (X1) and critical thinking (X2) towards their expository writing skills (Y). The research was conducted at SDN Wilayah Binaan I Makassar, East Jakarta, for the academic year of 2019/2020. This study was a quantitative approach with a written test survey method that applied correlational techniques (connectedness). The study took the samples through cluster random sampling technique. The results of the analysis showed that (1) there was a strong correlation of the students’ sentence structure mastery and expository writing skills; (2) there was a strong correlation of the students’ critical thinking skills and expository writing skills; and (3) there was a very strong correlation of the students’ sentence structure mastery and critical thinking skills towards their expository writing skills.